"Health oriented environment in a general education establishment" special course for "Human health" specialty students - Bellorin-Herrera, O. M.; Kаbаtska, O. V. (Харківський національний педагогічний університет ім. Г. С. Сковороди, 2014)
The article analyses the present day state of the problem of the pedagogical staff readiness for health-oriented school environment creation. On the results of the pilot research on the readiness of both working and future health basics teachers for health oriented school environment creation a number of problems in the methodological training of the staff has been revealed. Grounding on the results of the experiment results and scientific and methodological literature analysis the "Health Oriented Environment in a General Education Establishment" special course program has been developed. The special course program comprehension will facilitate future health basics teachers to master efficient methods of health oriented school environment creation, which will promote, in the result, their integral professional readiness for provision of the functioning of the environment in a general educational establishment oriented on preservation and improvement of health of all educational process participants.

У статті проаналізовано сучасний стан проблеми готовності педагогічних кадрів до створення здоров'яорієнтованого шкільного середовища. За підсумками пілотажного дослідження готовності працюючих та майбутніх учителів основ здоров'я до створення здоров'яорієнтованого шкільного середовища виявлено низку проблем щодо методичної підготовки педагогічних кадрів до цієї роботи. На підставі результатів експерименту та аналізу науково-методичної літератури розроблено програму спецкурсу "Здоров'яорієнтоване середовище загальноосвітнього навчального закладу". Засвоєння програми спецкурсу допоможе майбутнім учителям основ здоров’я опанувати ефективні методи створення здоров’яорієнтованого шкільного середовища, що в підсумку сприятиме формуванню в них цілісної професійної готовності до забезпечення функціонування в загальноосвітньому навчальному закладі шкільного середовища, орієнтованого на збереження та зміцнення здоров'я всіх учасників освітнього процесу.
Спецкурс "Здоров'яорієнтоване середовище загальноосвітнього навчального закладу" для студентів спеціальності "Здоров'я людини"
Keywords: methodological preparation; future health basics teacher; health oriented school environment; special course; методична підготовка; майбутній учитель основ здоров'я; здоров'яорієнтоване шкільне середовище; спецкурс